ON THE MACROECONOMIC DETERMINANTS OF CREDIT DELINQUENCIES IN THE USA (Revista de Estudos Sociais, 2024)
This investigation focuses on studying the impact of unemployment and income on debt delinquency. Auto loans, credit cards, mortgages, and student loans were used in the United States of America (USA) to perform this analysis. Panel data was used in the District of Columbia and the 50 states of the USA, with annual data from 2003 to 2019. In addition, a panel ARDL model was used for each type of loan. The study's innovation is researching the spread of unemployment to study the effect of unemployment on debt delinquency. The major findings of this research are trifold, (i) the determinants of the delinquency and default rate revealed only to share a limited number of determinants, (ii) the delinquency and default rate vary in complexity, and (iii) there is evidence that debtors arbitrage between credits if they have to enter in default. Most determinants have opposite impacts on the delinquency and default of borrowers. This fact means that policymakers must use a mix of instruments to minimize the delinquency end default globally. Policymakers also have to be aware of temporal inconsistencies, with short- and long-run contrary signs.